Исследование собственных колебаний пологих оболочек с использованием метода R-функций и сплайн-аппроксимации - Курпа, Лидия Васильевна; Осетров, Андрей Александрович (Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, 2007)
Natural vibrations of isotropic shallow shells with given plan form and different boundary conditions are investigated. The mathematical statement is constructed according to the classical theory. The given problem is solved by a variation-structural method using spline-approximation of undefined components of the structure of solution. Comparison of obtained numerical results with that already known illustrates the effectiveness of the offered method and created software. Numerical results for eigenfrequencies and natural modes of shells of different curvature with holes are presented.
Study of natural vibrations of shallow shells using R-functions method and spline-approximation
Keywords: методы вариационные; гипотезы Кирхгофа-Лява; метод Ритца